Galilæa, jord og den historiske Jesus - Jensen, Morten Hørning (Dansk Teologisk Tidsskrift, 2008)
The socio-economic conditions of Roman Galilee have been discussed intensively in recent years, mainly due to the question’s centrality in the research on the Historical Jesus. Was Galilee on the brink of meltdown or rather in a more prosperous condition? This article intends to further this discussion by focussing on the issue of land ownership. The aim is to see if land was rapidly being moved from independent or semi-independent small-plot owners to large estates controlled by the elite. If so, there is an obvious background for interpreting the Historical Jesus as a rebel against economic oppression. If not, the decisive factors behind the Jesus movement may better be found in a more complex setting with a variety of factors including also an eschatological and religious motivation.